2020
DOI: 10.29333/ejosdr/7864
|View full text |Cite
|
Sign up to set email alerts
|

Biofuel Certification Performance: A Review & Analysis

Abstract: The biofuel performance certification's scope is reviewed. An operational definition of biofuel performance certification has been developed. The certification of biofuel performance has been recognized as an effective assessment methodology and tool to manage biofuel consumption and improve biofuel performance systematically. It is found that a biofuel performance certification method is required in biofuel industry and biofuel research to authenticate the biodiesel and its blends for use in diesel engine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Certification of biofuel performance has been recognised as an effective methodology and evaluation tool to manage biofuel consumption and systematically improve biofuel performance. It has been found that a biofuels certification method is needed in the biofuels industry to authenticate biodiesel and its blends for use in diesel engines [1]. A standard energy audit method is required to evaluate the feasibility of biodiesel blend as fuel and also harmonise the research of biodiesel as fuel [2].…”
Section: Introductionmentioning
confidence: 99%
“…Certification of biofuel performance has been recognised as an effective methodology and evaluation tool to manage biofuel consumption and systematically improve biofuel performance. It has been found that a biofuels certification method is needed in the biofuels industry to authenticate biodiesel and its blends for use in diesel engines [1]. A standard energy audit method is required to evaluate the feasibility of biodiesel blend as fuel and also harmonise the research of biodiesel as fuel [2].…”
Section: Introductionmentioning
confidence: 99%